TECHNICAL FUNCTIONAL QUALITY INFLUENCE AND IMAGE ON STUDENT DECISIONS TO CHOOSE POSTGRADUATE - Djatola, Hariyanto; Hilal, Nur (Jurnal Sosial Humaniora, 2023)
This research aims to know the contribution of functional quality indicator, technical and image on student’s decision to choose Tadulako University Postgraduate Program. This is a survey reseaarch involving 219 sample which have been determined by accidental sampling technigue. To test proposed hypothesis, this research employs multiple linear regression. The result show that F value 51,72 at the significant level of 0,000. This means that all independent variables i.e, functional quality (X1), technical (X2) and image (X3) perform significant effect on student’s decision. Partially, functional quality (X1) indicates t value 2.044 which means that fuctional quality performs a significant effect on student’s decision. Technical quality (X2) indicates t value 2.300 which means that technical quality performs an effect on student’s decesion. It is found that image is the most dominant variable influencing students to choose postgraduate program at Tadulako University. This is indicated by t value 3.900 which higher that t table 1.645.